Faktor yang mendorong terjadinya penghakiman massa yang terjadi di wilayah Madura - Miswah, Miswah (Maliki Interdisciplinary Journal, 2024)
Massse judgment often occurs among society due to the growing of engineering actors against law-ordered existing orders in a region when no parties are willing to mediate the issue of this violation. This engineering action is commonly provoked by one of the affected or feared in the person. The actions made can, burn off-law offending law, beat him, until death, and many other types of torture. In general, this engineering perpetrator is the community in the interior of the interior or a corner of which lack of education or socialization of the law so that they have no consciousness of applicable law. In the article that the author makes for the appliance that occurs in the Madura area.